Pushed aside: Parentheticals, Memory and Processing - Dillon, Brian (2013)
In the current work, we test the hypothesis that ‘at-issue’ and 'not-at-issue' content (Potts, 2005) are processed semi-independently. In a written rating study comparing restrictive relative clauses and parentheticals in interrogatives and declaratives, we observe a significantly larger length penalty for restrictive relative clauses than for parentheticals. This difference cannot be attributed to differences in how listeners allocate attention across a sentence: a second study confirms that readers are equally sensitive to agreement violations in at-issue and not-at-issue content. A third rating experiment showed that the results do not depend on the restrictive relative clause intervening on the subject-verb dependency. A final experiment showed that the observed effects obtain with definite determiners and demonstratives alike. Taken jointly the results suggest that the parenthetical structures are processed independently of their embedding utterance, which in turn suggests that syntactic memory may be more differentiated than is typically assumed.